Exploring infill pattern and density effects on the tensile properties of 3D printed ABS - Bruno Leonardelli; Cesar Pandolfi; Gustavo Alberto Ludwig; Cristian Padilha Fontoura (Dyna)
Fused Deposition Modeling (FDM) is recognized as an efficient method for creating durable, complex parts quickly and affordably. This study examines how different infill patterns and densities affect the mechanical properties of ABS, with specimens produced via FDM for tensile testing. Fourier-transform infrared spectroscopy with attenuated total reflection (FTIR-ATR) identified the functional groups in ABS, while microscopic analysis assessed layer bonding. Results showed that tensile strength increased with higher infill densities and revealed that bonding characteristics of various infill patterns significantly impacted mechanical performance at densities from 25% to 100%. Interestingly, the same infill pattern displayed varied mechanical and bonding properties depending on density, highlighting the importance of selecting optimal infill configurations for specific applications.